Money Laundering: Civil Liability at Common Law and in Equity - Brindle WC, Michael (Journal of Malaysian and Comparative Law, 2007)
This is the text of a public lecture delivered at the Faculty of Law of the University of Malaya, Kuala Lumpur, Malaysia on 27 October 2007.